2021
DOI: 10.3390/su13095041
|View full text |Cite
|
Sign up to set email alerts
|

Estidama and the Pearl Rating System: A Comprehensive Review and Alignment with LCA

Abstract: Multiple sustainability standards and rating systems have been developed to draw attention to constructing sustainable buildings. The Pearl Rating System (PRS) is a mandate for all new construction projects in Abu Dhabi. Hence, it is important to understand the main components, advantages, and limitations of the PRS. The feasibility and the practical relevance of the PRS are still being studied. This paper addresses this gap and critically evaluates the PRS against some of the well-established rating systems l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In addition, there are the Australian Green Star, the French HQE and many more certification systems across the world. See Figure 5 for the list of green building certification systems globally [68]. This was followed by the release of the Leadership in Energy and Environmental Design (LEED) in the United States in 2000 [67]; however, LEED has continued to grow and includes new systems for existing buildings and entire neighbourhoods [67].…”
Section: Sustainable/green Building Certification Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are the Australian Green Star, the French HQE and many more certification systems across the world. See Figure 5 for the list of green building certification systems globally [68]. This was followed by the release of the Leadership in Energy and Environmental Design (LEED) in the United States in 2000 [67]; however, LEED has continued to grow and includes new systems for existing buildings and entire neighbourhoods [67].…”
Section: Sustainable/green Building Certification Systemsmentioning
confidence: 99%
“…In addition, there are the Australian Green Star, the French HQE and many more certification systems across the world. See Figure 5 for the list of green building certification systems globally [68].…”
Section: Sustainable/green Building Certification Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [16] investigated integrating LCA into the Green Standard for Energy and Environmental Design (G-SEED) in South Korea, the study proposed a conceptual framework to integrate the LCA of seven major building materials into the G-SEED rating system. Ramani & García De Soto [15] evaluated the assessment method of the Pearl Rating System (PRS) in Abu Dhabi based on LCA, the study has found that LCA is superficially included in the PRS rating system. LCA has been recently incorporated into the "Materials" category of Green Star, the Australian GBRS [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has been conducted to investigate LCA integration into the international GBRSs [14][15][16][17]. Most studies related to LCA integration into GBRSs focused on energy use and carbon emissions during the operational stage [18].…”
Section: Introductionmentioning
confidence: 99%